Pelatihan sistem informasi pengendalian stunting pada remaja putri di desa sawangan melalui penanggulangan anemia - Paradise Paradise; Wahyu Adi Prabowo; Gladi Pawestri Utami; Amalia Beladinna Arifa; Aulia Burhanuddin; Rifki Adhitama (LPPM IT Telkom Purwokerto, 2024)
Stunting and anemia in adolescent girls are major health issues in Indonesia, including in Sawangan Village Banyumas Regency. This research aims to implement stunting prevention strategies through the management of anemia in adolescent girls in Sawangan Village and to increase community awareness and knowledge about the importance of early prevention of stunting and anemia. The method is a participatory approach involving adolescent girls and local health workers. This activity includes socialization and training on stunting and anemia prevention, using hemoglobin check tools, and the provision of Blood Addition Tablets (TTD). In addition, an anemia monitoring system based on information technology is also implemented to monitor the condition of hemoglobin in adolescent girls regularly and structured. The results of this activity show an increase in community awareness and knowledge about the importance of preventing stunting and anemia, as well as an increase in monitoring and handling of these conditions. In addition, implementing an anemia monitoring system based on information technology has facilitated the regular and structured monitoring of hemoglobin conditions in adolescent girls. The contribution of this research is to achieve the target of Stunting Free Indonesia in 2030. With the implementation of stunting prevention strategies through the management of anemia in adolescent girls, this research contributes to improving the health and welfare of the community in Sawangan Village and supporting government efforts in achieving these goals.”